Surgical Management of Postpartum Perineal and Rectovaginal Injuries - Asif Mehmood, Bushra Nabi, Saima Zulfiqar, Hafsa Mubashir, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: The causes of maternal morbidity would be postpartum perineal and rectovaginal injuries such as obstetric anal sphincter injuries and rectovaginal fistulas, which are caused by vaginal delivery. Unless addressed in a timely fashion, these injuries may have long-term physical, psychological and social consequences. The surgical repair continues to be the primary mode of treatment, especially when the injury is moderate to severe, however, the results are inconsistent due to the timing of undertaking the surgery, the extent of injury and surgical skills. Objective: To assess the trend, surgical intervention measures, and prognoses of postpartum perineal and rectovaginal trauma treated in a tertiary care hospital in Peshawar. Methods: This retrospective observational study was based on the review of medical records of women surgically managed because of postpartum perineal and rectovaginal injuries within a 5 year time. The outcomes measured were demographic factors, obstetric risk factors, nature and degree of injury, time and surgical repair type, postoperative complications, and functional outcomes at follow-up. Primary repair was compared with delayed surgical repair of the defects within 24 hours. Results: One hundred and sixty-two patients were included. The most frequent injury was third-degree perineal tears, and the others were the fourth-degree tears and the rectovaginal fistulas. Primary repair was done immediately in 64.2 percent of cases and was linked to an increase in uneventful repair and less postoperative problems than delayed repair. The overall success in surgery was excellent with majority of patients recording satisfactory anatomic and functional results. Cases that were delayed and complicated were more prone to complications and recurrence. Conclusion: Postpartum perineal and rectovaginal injuries are treated by means of timely surgical repair, which brings good results. There is a need to strengthen the systems of early recognition and referral to minimize maternal morbidity. Keywords: post-partum perineal injury; obstetric anal sphincter injury; rectovaginal fistula; surgical repair.